Control to compensate reactive power at medium voltage load nodes to improve performance and load voltage stabilization based on modular multilevel converter - Cuong, Tran Hung; Tung, Nguyen Nhat; Anh, An Thi Hoai Thu (Institute of Advanced Engineering and Science, 2025)
This paper will present a reactive power control method for medium voltage power grids based on the modular multilevel converter (MMC) structure. In particular, the MMC converter applies control algorithms to operate as a D-STATCOM device. A proportional–integral (PI) controller combined with an improved nearest level modulation (NLM) method performs the system control process. The purpose is to create sinusoidal voltage levels on the alternating current (AC) side to generate or absorb reactive power according to load requirements. This will ensure that the amount of reactive power for the load node is always within the allowable value and improve voltage quality, increasing the power factor for the load. Verifying and evaluating results are performed on MATLAB/Simulink software.